SIGNS IN DAUD KIM'S STATEMENTS ON HIS YOUTUBE CHANNEL: THE CORRECTIONS OF MISTAKEN ISLAMIC UNDERSTANDING - Mia Ananda Derasta; Yuyun Nurulaen; Dian Nurrachman (CALL, 2022)
ABSTRACT The study aimed to examine icons, indices, and symbols in Daud's speech connected to misconceptions about Islam through the semiosis method. Semiotics can be used in a variety of contexts. therefore, it is crucial to conduct study in this area to prevent misconceptions about Islam. The study has two issues: (1) the semiotic indicators in Daud Kim's vlog that are connected to misinterpretations of Islamophobic messaging (2) Daud Kim's vlog discusses misinterpreting messages about Islam's semiosis process. In order to reply to and examine the problems, Peirce's theory of triadic relation was used which illustrates the relationship between the represent, object, and interpretation in semiotics. The description of the semiosis process and how it relates to how the indicators should be interpreted were made evident in this study using the qualitative technique. The research's semiosis process: Every statement—verbal or nonverbal—began as a representamen, progressed to an object as the first point at that statement, and—from the relationship between representamen and object—became the interpretant in the end. As a consequence, the study discovered that Daud's statement can be strengthened by the semiosis process in order to avoid and clarify the mistaken message about Islam. It is possible to understand as far as feasible, the essence of the Islamic message through representation, object, and interpreter. Keywords: semiosis, Daud Kim, icon, index, and symbol